(3CSGSjGJ Yde GdEOGQI GdJWHjbjs - (3fHjd eMeO(B, (3eQSis ((3GdEScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2006)
(3ebOeI aj GdJMdjd Gdcej(B- (3JWHjb GdfeGPL GdQjGVjI aj GdJMdjd Gdcej(B- (3GdHQeLI GdNWjI (B((3CSdhH GdMd GdHjGfj(B)- (3CSdhH GdSeHdcS(B- (3JMdjd GdMSGSjI hGdfXQjI GdKfGFjI(B- (3feGPL Gdfbd(B- (3HQeLI GdCYOGO GdUMjMI(B- (3HQeLI GdGgOGa hGdHQeLI ZjQ GdNWjI(B- (3GdfeGPL GdTHcjI(B- (3feGPL HjQJ hGdeSGQ GdMQL(B- (3feGPL GdeNRhf(B- (3feGPL Uaha GdEfJXGQ(B- (3JMdjd GdbQGQGJ(B- (3GdHQeLI GdOjfGejcjI(B- (3fXQjI GdeHGQjGJ(B.s
Keywords: (3GdHQeLI GdNWjIs; (3GdJMdjd GdQjGVjs; (3GdJMdjd Gdcejs